PENGARUH KUALITAS BAHAN BAKU DAN PROSES PRODUKSI TERHADAP KUALITAS PRODUK PADA PT. TUT CIKARANG - Nurul Giswi Karomah; Himawan Pramulanto; Pebry Septian Nugraha (Fakultas Ekonomi dan Bisnis, Universitas Jayabaya, 2023)
The purpose of this study was to determine the effect of the quality off raw materials and production processes simultaneouslyy (simultatneosly) or individually (partially) on product quality at PT TUT Cikarang. The sample in this study were 117 respondents. The technique used is probability sampling technique. The data ccolletion technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear analysis. The results of this study indicate that: (1) the quality of raw materials is significant for product quality at PT TUT Cikarang proven by significant value of 0.003 <0.05, then (2) the production process has significant value of 0.000 < 0.05, and (3) the quality of raw materials and production processes has a significant effect on product quality at PT TUT Cikarang, as evidenced by the test results obtained a calculated F value of 273, 875 with a significance of 0.000<0.05. Keywords:Quality of raw materials, Production processes, product quality.